Reviving forgotten crops: Leveraging underutilised iron-rich plant foods to combat anemia in India - Swati Nishad; Virginia Paul
Anemia is a condition characterized by a reduced level of red blood cells or haemoglobin, which negatively impacts an individual's work capacity. The World Health Organization (WHO) and the Food and Agriculture Organization (FAO) recommend four key strategies to address micronutrient deficiencies: nutrition education, food fortification, supplementation, and dietary diversification. Despite the implementation of various supplementation and fortification programs, anemia remains a growing global concern, particularly in low- and middle-income countries. To enhance the effectiveness of anemia management, a comprehensive approach combining multiple dietary strategies$1 (Bsuch as dietary diversification and nutrition education$1 (Bshould be adopted. Although a wide range of iron-rich foods with significant nutritional benefits is available globally, many remain underutilized due to the increasing preference for processed foods. The Indian Food Composition Table highlights several traditional, affordable, and locally available iron-rich foods. This review explores dietary strategies for preventing iron deficiency, focusing on the nutrient profile and health benefits of underutilized plant-based iron-rich foods. Beyond their high iron content, these foods offer additional nutritional advantages and play a valuable role in anemia prevention. Recent studies on food product development incorporating these underused ingredients have also been examined. Literature suggests that numerous global studies have investigated iron- rich sources that were once staples in the traditional Indian diet. These studies demonstrate that products developed from such foods offer various health benefits. However, raising public awareness through nutrition education remains crucial to encourage the adoption of these untapped, healthier food options.s